UNAIDS Global AIDS Update 2024 - UNAIDS (United Nations, 2024)
The report titled The Urgency of Now: AIDS at a Crossroads, demonstrates the HIV response is at a crossroads: success or failure will be determined by which path leaders take. The report shows that the decisions leaders make this year will determine whether AIDS is ended as a public health threat by 2030. Taking the wrong path, by limiting resourcing or clamping down on human rights, would lead the pandemic to continue to grow, costing millions more lives and undermining global health security.